The hepatoprotective role of the aqueous extract of ginger against the harmful effects of paracetamol in rats - Jameela Abd-ALHassan (University of Thi-Qar Journal of Science, 2019)
This study was performed to determine the hepatoprotectiveactivities of watery extract of ginger in hepatotoxicity induced by paracetamolin albino rats. Twenty fourrats were used and divided randomly into four equal groups each ofwhich contain six animals, the first one was served as control, received nomal saline only, the second group werereceived paracetamol at a single dose of 3g/kg/B.W orally to induce hepatotoxicity, and the third and fourth groupsreceived watery extract of ginger at a dose 200 mg/Kg & 400 mg/Kg B.W orally once daily for 3 days respectivelyfollowed by administration of single dose of paracetamol 3 g/Kg B.Wafter 30 minute after extracts administration. Liverfunctions were assessed by estimating serumalanine amino transferase (ALT) , aspartate amino transferase (AST) ,alkaline phosphatase (ALP), total serum bilirubin & total serum protein & albumin . The results revealed that the use ofgenger extracts at each dose ( 200 mg/Kg , 400 mg/Kg B.W) produced significant reduction in the level of theseenzymes , total bilirubin while caused significant increase in the levels of total serum protein & total serum albumin ,so the use of ginger extracts possess hepatoprotective activity by restoring the normal hepatic functions and potentiatingthe bio- defense system of the liver against hepatotoxicity produced by paracetamol administration